Incorporation of O6-methylguanine restricts the conformational conversion of the human telomere G-quadruplex under molecular crowding conditions. Issue 9 (17th December 2015) - Zhao, Andong; Zhao, Chuanqi; Tateishi-Karimata, Hisae; Ren, Jinsong; Sugimoto, Naoki; Qu, Xiaogang
Abstract : O 6 -methylguanine incorporation impeded the conformational conversion of G-quadruplex from a hybrid to a parallel structure under molecular crowding conditions. Abstract : Here we systematically studied the incorporation of O 6 -methylguanine (6mG) into different positions of the human telomere G-quadruplex. In contrast to the natural G-quadruplex, the 6mG incorporated G-quadruplexes impeded the conformational conversion of the G-quadruplex from a hybrid to a parallel structure under molecular crowding conditions in a K + containing buffer.